Review of Red Sea Xenisthmus Snyder (Teleostei: Gobioidei: Xenisthmidae), with description of a new species - Gill, Anthony C.; Bogorodsky, Sergey V.; Mal, Ahmad O. (Zootaxa, 2017)
Three species of the xenisthmid genus Xenisthmus Snyder are recorded from the Red Sea. Xenisthmus polyzonatus (Klunzinger), the only described species previously known from the Red Sea, is reported on the basis of eight specimens from Egypt, Eritrea and Saudi Arabia. Xenisthmus oligoporus new species is described from four specimens, 17.7–25.0 mm SL, from Sudan and Saudi Arabia. It is distinguished from all other congeners in having a reduced number of cephalic sensory pores and 14–15 segmented rays in the second dorsal fin. Xenisthmus balius Gill & Randall is newly recorded from the Red Sea on the basis of 13 specimens from Eritrea, Egypt and Saudi Arabia. The new specimens of this species are described and compared with previously known specimens, the holotype and eight paratypes from the Arabian (= Persian) Gulf. All three species are described in detail and illustrated with colour photographs. An identification key to the species is also provided.